C - Deitel, H. M. (Prentice Hall, 2004)
This text introduces fundamental notions of structured programming and software engineering and progresses quickly to more intermediate material. It covers the full C language, key library functions, object-oriented programming in C++ and Java, and event-driven GUI programming in Java.